Bibliometric analysis of Islamic banking publication in the post-COVID-19 pandemic era - Hasan, Zulfikar (Faculty of Business and Management, 2025)
The deconstruction aims to achieve a comprehensive understanding of Islamic banking and its relationship with Covid-19 through bibliometric analysis. The model analysed 200 papers published between 2020 and 2023, utilizing the Scopus database with the keywords "Islamic banking in the Covid-19 pandemic era." This analysis employed VOSviewer software and Publish or Perish to provide a visual representation of bibliometric data and the effects of the analysis. The first article published during the Covid-19 pandemic in 2020 appeared in the Journal of Islamic Marketing, authored by D. Suhartanto from Indonesia. In 2020, there were 103 publications, while in 2023, the number decreased to 97. The decline in the number of published journal articles related to Islamic banking from 2020 to 2023 is not substantial, as it reflects a difference of only 6 articles. This research presents current publications on the topic of Islamic banking worldwide, thereby supporting the development of guidelines for the perseverance of Islamic banking. The findings of the study also establish a connection between Islamic banking activities and academic associations. Furthermore, the researcher's commitment to continue studying Islamic banking during the Covid-19 pandemic, and behind it evolves endemic. Through the bibliometric analysis, the emerging topic of the Covid19 pandemic in the field of Islamic banking can be effectively reviewed, offering a systematic and transparent overview of the literature. As Islamic banking is an evolving financial specialization, there is a pressing need for a more global interpretation of this banking strategy.